The integration of the new technologies of the information and the communication in the school. Basic factors - Bernardo GARGALLO LÓPEZ; Jesús SUÁREZ RODRÍGUEZ (Ediciones Universidad de Salamanca, 2016)
The information and communication new technologies have constructed a new context: the information society, in which the school will experience important changes necessarily. The integration of these new technologies in education will be adequate if it is made from an active and constructive pedagogical perspective. In that dynamics, there is a set of very important factors for an effective integration: the institutional support and the development of pertinent policies, which involves infrastructures and training of teachers, the support of the managing teams of the schools, and the development of coherent models of evaluation.